2013
DOI: 10.1186/1471-2164-14-181
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recovery of proteins from multiple source samples after trizol® or trizol®LS RNA extraction and long-term storage

Abstract: BackgroundSimultaneous isolation of nucleic acids and proteins from a single biological sample facilitates meaningful data interpretation and reduces time, cost and sampling errors. This is particularly relevant for rare human and animal specimens, often scarce, and/or irreplaceable. TRIzol® and TRIzol®LS are suitable for simultaneous isolation of RNA, DNA and proteins from the same biological sample. These reagents are widely used for RNA and/or DNA isolation, while reports on their use for protein extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 36 publications
3
111
0
Order By: Relevance
“…Total RNA was extracted from RAW264.7 cells by Trizol reagent (Invitrogen, Corp., Carlsbad, USA), according to the manufacturer's instructions [23,24]. Quantitative determination of RNA was conducted using the GeneQuant pro RNA/DNA Calculator spectrophotometer (Amersham Biosciences, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from RAW264.7 cells by Trizol reagent (Invitrogen, Corp., Carlsbad, USA), according to the manufacturer's instructions [23,24]. Quantitative determination of RNA was conducted using the GeneQuant pro RNA/DNA Calculator spectrophotometer (Amersham Biosciences, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded in 6-well culture plates at a density of 1 × 10 6 cells/ well and serum-starved for 18 h. Cells were then pretreated with resveratrol for 1 h and stimulated with 1 μg/ml LPS for 4 h. Total RNA was isolated from cells using TRIzol reagent following the manufacturer's instructions [18], and complementary DNA was synthesized using 3 μg of RNA in a reverse transcription reaction from real-time polymerase chain reaction (RT-PCR) kit (Invitrogen, Carlsbad, USA). Quantitative RT-PCR (qRT-PCR) analyses were performed using C1000 thermal cycler (Bio-Rad) with SYBR-Green (Invitrogen).…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Urea, a chaotropic salt, was investigated for its ability to disrupt hydrogen bonding (33) and reduce hydrophobic interactions (34), the two key interactions involved in peptide self-assembly into -sheet rich fibers (35). In fact, urea has been noted to increase protein yield following protein precipitation (36) and together with thiourea was shown to significantly improve protein solubilization (37,38). Moreover, it has been shown that urea is an effective agent for solubilizing poorly soluble (hydrophobic) membrane-associated proteins (39), proving more effective than RIPA buffer when tested with small heat-shock proteins (40).…”
Section: Resultsmentioning
confidence: 98%